Avaliação da capacidade resistente de vigas de concreto armado reforçado com fibras utilizando os procedimentos normativos da ABNT NBR 16935:2021 - Jacomini, Guilherme Martins (Universidade Federal de São Carlos, 2021)
Fiber Reinforced Concrete (FRC) is a composite that has improved mechanical properties when compared to plain concrete. The addition of fibers in the cementitious matrix of concrete aims to improve the performance of the material, providing crack control and a post-cracking deformation capacity increase. Thus, the demand for this material has increased in recent decades, being more commonly applied to pavements and tunnel lining, being possible to use it in linear elements. For the use of FRC in structural members, steel fibers are mainly used because they provide better mechanical responses when required for different loads. For application in structural projects, it is necessary to use design methods that guarantee the safety and performance of the members. However, in Brazil, the current standard on the procedures that must be adopted for the use of the FRC in design, ABNT NBR 16935: 2021, was recently published and studies that apply this methodology are still rare in the literature. In this context, the present work aims to use the design procedures presented by ABNT NBR 16935: 2021, as well as a comparative study between the results of the resistant capacity of linear members obtained experimentally and by the design method. Thus, the studies conducted in this work demonstrate that the normative procedures tend to overestimate the resistant capacity of the analyzed beams, however, these values appear to be similar to those found in the literature when applying the procedures of the fib Model Code (2012). The application of the constitutive laws can demonstrate the influence on the reinforcement rate of the members as the fiber content is altered, being able to obtain a 10% reduction in the value of the longitudinal reinforcement.
Evaluation of the resistant capacity of fiber reinforced concrete beams using the normative procedures of ABNT NBR 16935:2021
Keywords: Concreto reforçado com fibras; ABNT NBR 16935:2021; dimensionamento; elemento estrutural; Fiber reinforced concrete; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS